Świat ziemiański w poezji polskiej: od renesansu do połowy XIX wieku. Ciągłości i zmiany - Kostkiewiczowa, Teresa (Poznańskie Studia Polonistyczne. Seria Literacka, 2025)
The poetry of the Polish landed gentry drew on the ancient models of Horace and Virgil: on their images of the farmer-ploughman, the family, and the cyclical rhythms of nature. It also established an ethos of work, moderation, self-sufficiency, and freedom. In the 18th century, the perspective shifted: the home ceased to be a fixed living space, becoming more of a space of otium, a refuge from the court and the city while remaining a symbol of security and moral order. Individual images of gardens, seasons, and stages of human life began to appear in poetic works. After the partitions, the motif of farm work took on a patriotic dimension in which cultivating the land signified fidelity to tradition and freedom. The home of the landed gentry became etched in the Polish imagination as a space of harmony and enduring values, independent of time and history.